Antarctic benthic species distribution models and compositional analysis in a coastal ecosystem under glacier retreat - Neder, Camila (2024)
In the face of global climate change, the West Antarctic Peninsula has been identified as highly vulnerable due to rising temperatures and increased anthropogenic carbon emissions impacting its biodiversity. Species distribution models are useful tools for assessing habitat suitability and forecasting responses in a changing environment. At Potter Cove, glacier retreat has opened new ice-free areas for colonization while altering the environment through meltwater input and sediment run-off. This fjord serves as a case study to identify environmental predictors driving Antarctic zoobenthos distribution in a changing coastal ecosystem and to analyze the potential benthic colonization in areas strongly affected by glacier retreat. About 60% of the study area, equivalent to 5.45 km2, was estimated to be suitable for zoobenthic occurrence. Potential spatial co-occurrence was identified in highly glacier-influenced areas. The interpretation of binary transformation thresholds emphasizes taxa-specific environmental requirements responding to glaciological, oceanographic, and sedimentological predictors, inferring particularities depending on their feeding strategies. A lower threshold value estimated a wider habitat extension. This study enhances our understanding of benthic responses to ongoing environmental shifts due to climate change in the Antarctic coastal ecosystem, emphasizing long-term research to increase our current predictive capacities and improve conservation and management strategies.